PEDAGOGICAL CONDITIONS OF ACTIVE FORMATION COMMUNICATIVE POSITION OF STUDENTS - D.V. Sherbyna (Academy of Cognitive and Natural Sciences, 2007)
The article investigates pedagogical condition of formation and development of active communicational position of pupils in teaching and educational process.